2010
DOI: 10.1108/01437721011066335
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐return trade‐offs to different educational paths: vocational, academic and mixed

Abstract: Purpose -This paper investigates the rates of return and the risks of different types of educational paths -all leading to a tertiary educational degree. We distinguish a purely academic educational path from a purely vocational path and a mixed path with loops through both systems.Design/methodology/approach -To study the labor market outcome we compare earnings and calculate net return rates as well as risk measures to investigate whether different educational paths are characterized by different risk-return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 37 publications
(39 reference statements)
2
15
0
Order By: Relevance
“…In a second robustness check we use a different sample. As the type of university could influence labour market entry and career development differently (Dearden et al ., 2002; Tuor and Backes‐Gellner, 2010), we estimate all models only for tertiary academic education, dropping graduates of universities of applied sciences (see Tables A6 and A7 in Appendix). This robustness check shows very similar effects of ‘earning while learning’ as in our basic analysis and thus confirms our findings.…”
Section: Resultsmentioning
confidence: 99%
“…In a second robustness check we use a different sample. As the type of university could influence labour market entry and career development differently (Dearden et al ., 2002; Tuor and Backes‐Gellner, 2010), we estimate all models only for tertiary academic education, dropping graduates of universities of applied sciences (see Tables A6 and A7 in Appendix). This robustness check shows very similar effects of ‘earning while learning’ as in our basic analysis and thus confirms our findings.…”
Section: Resultsmentioning
confidence: 99%
“…One notable exception is Switzerland, 2 a country with an extensive vocational education system that attracts two-thirds of the individuals in every cohort (Tuor and Backes-Gellner, 2010). The Swiss educational system allows students to achieve tertiary education degrees for both academic and vocational tracks.…”
mentioning
confidence: 99%
“…In , using regional stratification and rare events of entrepreneurial events, it is found that the generalist notion is supported. See also Backes-Gellner et al (2010) and Tuor and Backes-Gellner (2010). tions have significantly increased productivity in the past and could also do so in the future.…”
Section: The Futurementioning
confidence: 96%